Realitas Sosial dalam Video Klip “Mangu” Karya Fourtwnty Ft. Charita (Persperktif Wacana Multimodal) - Ilma, Lu'lu'atul; Firmansyah, Mochamad Bayu; Rokhmawan, Tristan (Dinasti Research, 2025)
This study examines the social reality represented in the music video Mangu by Fourtwnty ft. Charita from a multimodal discourse perspective. The analysis focuses on the interplay of five modes language, image, music, sound, and movement that collectively construct emotional and social meanings. The research applies a qualitative descriptive method using Kress and van Leeuwen’s semiotic framework. Data were collected from the song lyrics, scenes, sound effects, and character movements in the video. The findings reveal that the poetic lyrics depict spiritual conflict and emotional separation, while visual elements such as warm tones, wooden houses, and dim lighting emphasize a nostalgic atmosphere. The minor-toned music with a slow tempo evokes sadness, whereas background sounds like door creaks and wind enhance realism. Minimalist body movements, including lowered gazes and turning away, symbolize uncertainty and resignation. The interaction of these modes reflects social realities of differing beliefs and existential confusion. This study highlights that music videos can serve as mediums of emotional and social reflection rather than mere entertainment.